Designed single-source precursors for iron germanide nanoparticles: colloidal synthesis and magnetic properties. Issue 42 (11th October 2018) - Sodreau, Alexandre; Mallet-Ladeira, Sonia; Lachaize, Sebastien; Miqueu, Karinne; Sotiropoulos, Jean-Marc; Madec, David; Nayral, Céline; Delpech, Fabien
Abstract : The substituent of single source precursors [iPrNC( t Bu)NiPrRGe]Fe(CO)4 (R = Cl, N(SiMe3 )2 ) has a dramatic influence on the synthesis of iron germanide nanoparticles. Abstract : The synthesis of iron germanide nanoparticles at the nanoscale is a challenging task. Here, we describe the preparation of nanocrystals of the hexagonal Fe1.67 Ge phase via the thermolysis of single source precursors [iPrNC( t Bu)NiPrRGe]Fe(CO)4 (where R = Cl, N(SiMe3 )2 ) under mild conditions (200 °C). These bimetallic precursors and the corresponding germylenes [iPrNC( t Bu)NiPrRGe] were fully characterized by spectroscopic techniques as well as single crystal X-ray diffraction. While the structural features of the molecular species were shown to be almost identical, the results of the thermolysis were highly dependent on the nature of R. When R = Cl, multimodal size distributions and non-controlled phases were obtained. In contrast, the thermolysis of [iPrNC( t Bu)NiPrN(SiMe3 )2 Ge]Fe(CO)4 yielded pure ferromagnetic Fe1.67 Ge nanoparticles with a mean diameter close to 6 nm and a narrow size distribution (<12%). These results were rationalized in terms of Ge–substituent bond energy thanks to a computational study.